Global Integrated Genomic and Transcriptomic Analyses of MYB Transcription Factor Superfamily in C3 Model Plant Oryza sativa (L.) Unravel Potential Candidates Involved in Abiotic Stress Signaling - Muthuramalingam, Pandiyan; Jeyasri, Rajendran; Selvaraj, Anthonymuthu; Shin, Hyunsuk; Chen, Jen-Tsung; Satish, Lakkakula; Wu, Qiang-Sheng; Ramesh, Manikandan (Frontiers in Genetics, 2022)
Plants transcription factors (TFs) are significant players in transcriptional regulations, signal transduction and constitute an integral part of signaling networks. MYB TFs is a major TFs superfamilies play pivotal roles in regulation of transcriptional reprogramming, physiological processes and abiotic stress (AbS) responses. To explore the understanding of MYB TFs, genome and transcriptome-wide identification was performed in the C3 model plant, Oryza sativa (OsMYB). This study retrieved 114 OsMYB TFs were computationally analyzed for their expression profiling, gene organization, cis-acting elements and physicochemical properties. Based on the microarray datasets, six OsMYB genes which were sorted out and identified by a differential expression pattern were noted in various tissues. Systematic expression profiling of OsMYB TFs showed their meta-differential expression of different AbS treatments, saptio-temporal gene expression of various tissues and their growth in the field and gene expression profiling in responses to phytohormones. In addition, circular ideogram of OsMYB genes in related C4 grass plants conferred the gene synteny. Protein-protein interactions of these genes revealed the molecular crosstalk of OsMYB TFs. Transcriptional analysis (qPCR) of 6 OsMYB players in response to drought and salinity stress suggested the involvement in individual and combined AbS responses. To decipher how these OsMYB play functional roles in AbS dynamics, further research is a prerequisite.